(untitled) (Vietnam Journal of Community Medicine, 2026)
Abstract: This cross-sectional descriptive study was conducted at Tien Giang Provincial General Hospital to assess the proportion of nurses with knowledge and practices regarding safe injection. Methodology:A census sample of 318 nurses working in clinical departments was included. Data were collected through structured observations using a checklist and direct interviews at Tien Giang Provincial General Hospital. Results:17.9% of nurses did not correctly understand the definition of safe injection. Additionally, 64.2%, 38.4%, 33.6%, and 37.4% of nurses lacked comprehensive knowledge about the objectives of safe injection, associated risks, causes, and appropriate management following needle-stick injuries, respectively. Compliance with safe injection procedures ranged from 75.2% to 87.7%. In conclusion, the knowledge and practices related to safe injection among nurses at Tien Giang Provincial General Hospital remain insufficient and not fully comprehensive.